ANESTEZJOLOGIA I INTENSYWNA TERAPIAGoal directed therapy – prevention of the complications in the early postoperative period - Kucewicz, Ewa; Drwiła, Rafał; Krawczyk, Karol; Kruczak, Wojciech; Prokopowicz, Jacek; Toczek, Krzysztof; Urbańska, Ewa; Ziętkiewicz, Mirosław; Misiołek, Hanna; Knapik, Piotr (Kardiochirurgia i Torakochirurgia Polska/Polish Journal of Thoracic and Cardiovascular Surgery, 2011)
There is evidence that perioperative goal-directed therapy (GDT) based on flow-related hemodynamic parameters improves patient outcome, particularly in high-risk patients. Mean arterial blood pressure and central venous pressure are routinely used to monitor hemodynamics but no information on blood flow can be obtained with MAP or CVP. Enhanced hemodynamic monitoring seems to be crucial in the guidance of perioperative volume therapy and cardiocirculatory support. We present different methodes of hemodynamic monitoring – pulmonary artery catheter, esophagus Doppler, FlowTrac/ Vigileo. PICCO, SvO2 and lactat concentrations. Using a optimization protocol based on enhanced hemodynamic variables it is possible to folow the results of the implemented therapy.